2001
DOI: 10.1210/endo.142.2.7958
|View full text |Cite
|
Sign up to set email alerts
|

Relative Enzymatic Activity, Protein Stability, and Tissue Distribution of Human Steroid-Metabolizing UGT2B Subfamily Members**This work was supported by the Medical Research Council of Canada, the Fonds de la Recherche en Santé du Québec, and Endorecherche.

Abstract: Androgens and estrogens play major roles in cell differentiation, cell growth, and peptide secretion in steroid target tissues. In addition to the binding of these hormones to their receptors, formation and metabolism are important in the action of steroids. Metabolism of the potent steroid hormones includes glucuronidation, a major pathway of steroid elimination in liver and several steroid target tissues. Glucuronidation is catalyzed by UDP-glucuronosyltransferases (UGTs), which transfer the polar moiety fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…No measurable expression of any UGT1A gene has been observed in human lung based on RT-PCR analyses [103]. UGT2B4, 2B7, 2B10, 2B11, 2B15, and 2B17 were identified in human lung [104]. It has been reported that beclomethasone dipropionate (BDP) stimulated the expression of mRNAs for UGT 2B4 and 2B11, and transporters such as multidrug resistance Pglycoprotein, multidrug resistance-associated protein 1 and 2 in cultured bronchial epithelial cells.…”
Section: Ugtsmentioning
confidence: 99%
“…No measurable expression of any UGT1A gene has been observed in human lung based on RT-PCR analyses [103]. UGT2B4, 2B7, 2B10, 2B11, 2B15, and 2B17 were identified in human lung [104]. It has been reported that beclomethasone dipropionate (BDP) stimulated the expression of mRNAs for UGT 2B4 and 2B11, and transporters such as multidrug resistance Pglycoprotein, multidrug resistance-associated protein 1 and 2 in cultured bronchial epithelial cells.…”
Section: Ugtsmentioning
confidence: 99%
“…The UGT isoform expression is tissue-specific, which is reflected by the fact that each UGT family member is expressed in selective tissues, and each tissue harbors the expression of multiple UGT isoforms. UGT1A1, 1A3, 1A4, 1A6, 1A9, and all the UGT2B isoforms have been shown to be expressed in the liver [10,11], whereas the human intestine has been shown to express UGT1A1, 1A6, 1A8, 1A10, and UGT2B7 [10,12]. The mechanisms underlying the tissue-specific distribution of UGT isoforms, have not been fully understood.…”
Section: Tissue-specific Distribution Of Ugt Isoformsmentioning
confidence: 99%
“…Interestingly, these two enzymes are the ones with the highest activity on steroid hormones within this family. 47 The A allele of rs4148298, which was associated with higher UGT2B7 expression in liver, 35 was correlated with smaller power law β value, and thus lower mammographic density (Fig. 3).…”
Section: Discussionmentioning
confidence: 97%